Legal Protection for Child Victims of Sexual Abuse in Palopo City: Islamic Criminal Law Perspective - Rahimuddin, Hastuti; Yusmad, Muammar Arafat; Assaad, Andi Sukmawati (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
The purpose of this study was to explore legal protection for child victims of sexual violence in the city of Palopo from the perspective of Islamic criminal law. The research method used was qualitative with interview and observation data collection techniques. The results of the study found that Sexual Violence against Children in the City of Palopo each consisted of two parts, namely: Verbal Violence in the City of Palopo, each of which was obtained by researchers amounting to 17 (seventeen) cases, and Physical Violence, acts of physical violence against Children at LPPA Luwu Raya in 2013. 2022/2023 proved 12 (twelve) cases, namely 9 (nine) cases of immorality in the form of abuse that had an impact on the physical. Furthermore, the Form of Legal Protection for Child Victims of Sexual Violence in the City of Palopo is to obtain protection for the safety of their person, family, and property and be free from threats from any party. In addition, in legal cases, child victims of sexual violence are not exposed like other criminal acts. Sexual harassment in the perspective of Islamic law does not have clear rules and provisions regarding detailed legal sanctions. So the legal provisions become a matter of ijtihad of scholars or the government that will produce legal provisions by referring to the legal provisions contained in the Qur'an and hadith. In another perspective, perpetrators of sexual harassment will be handed over to the judge or government who has the right to decide the case.